Compound molecular sieve ozone catalyst as well as preparation method and application thereof

Through the preparation of composite molecular sieve ozone catalysts, combined with the combination strategies of hydrophilic and hydrophobic molecular sieves, a catalyst with a multi-layer pore structure is formed, which solves the problem of traditional technology insufficient removal ability of difficult-to-degrade hydrophobic organic matter in recycled water, and achieves efficient organic matter removal effect.

CN119633894APending Publication Date: 2025-03-18BEIJING DRAINAGE GRP CO LTD
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411820895.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove hydrophobic organic matter in recycled water, and traditional ozone catalysts lack the ability to remove hydrophobic organic matter.

Method used

Using a composite molecular sieve ozone catalyst, the hydrophilic molecular sieve powder supported by the active component is mixed and granulated with the fluorinated hydrophobic molecular sieve powder, an inorganic binder and a pore-forming agent to form spherical catalyst particles with micropore-mesoporous-metaporous hierarchical pore structure.

Benefits of technology

It significantly improves the removal rate of difficult-to-degrade organic matter in recycled water, especially hydrophobic organic matter, and improves the anti-fouling performance and mechanical strength of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119633894A_ABST
    Figure CN119633894A_ABST
Patent Text Reader

Abstract

The invention discloses a compound molecular sieve ozone catalyst and a preparation method and application thereof, and the preparation method comprises the following steps: mixing molecular sieve powder with a low silica-alumina ratio and a salt solution of an active component, heating and stirring the mixed solution to evaporate the solvent, washing, drying, calcining and grinding the residual solid to obtain the compound molecular sieve ozone catalyst. Active component loaded hydrophilic molecular sieve powder is obtained; the preparation method comprises the following steps: mixing all-silicon molecular sieve powder and an NH4F aqueous solution, carrying out a hydrothermal reaction, and after the reaction is finished, washing, drying, calcining and grinding an obtained solid material to obtain fluorinated modified hydrophobic molecular sieve powder; mixing the active component loaded hydrophilic molecular sieve powder, the fluorinated modified hydrophobic molecular sieve powder, an inorganic binder and a pore forming agent, and granulating to obtain spherical catalyst particles; and drying and calcining the spherical catalyst particles to obtain the compound molecular sieve ozone catalyst. The ozone catalyst provided by the invention improves the removal rate of refractory organics in reclaimed water.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of water treatment, and more specifically, relates to a compound molecular sieve ozone catalyst and a preparation method and application thereof. Background Art

[0002] As the country continues to promote the recycling and utilization of sewage resources, the emission standards of some places and river basins require that the chemical oxygen demand (COD) meet the requirements of surface Class IV water (COD≤30mg / L) or even Class III water (COD≤20mg / L). However, after the secondary biological treatment process, most of the organic matter in the effluent is difficult to biodegrade, and the traditional deep treatment process cannot stably achieve the deep removal of difficult-to-degrade organic matter. Therefore, it is necessary to use activated carbon adsorption, advanced oxidation and other processes for deep treatment. As one of the advanced oxidation processes, heterogeneous ozone catalytic oxidation technology has the advantages of mild reaction process, no by-product generation and low operating cost, and is widely used in the field of difficult-to-degrade organic matter removal.

[0003] Heterogeneous ozone catalytic oxidation technology improves the removal effect of difficult-to-degrade organic matter by introducing a solid-phase catalyst. First, the dissolved organic matter and ozone in the water are adsorbed and enriched on the catalyst surface, which improves the mass transfer efficiency of ozone oxidation of organic matter; secondly, the Lewis acid sites on the catalyst surface undergo coordination exchange with water molecules to form surface hydroxyls, which then react with ozone to generate hydroxyl radicals, thereby mineralizing and removing difficult-to-degrade organic matter. At present, the more common ozone catalysts can be divided into two categories: activated carbon-based and metal oxide-based. Among them, activated carbon-based ozone catalysts usually have a developed pore structure and abundant surface oxygen-containing groups, but have low mechanical strength, are easy to break and lose during use, and have a short service life. The surface structure of metal oxide-based ozone catalysts is more stable, and its common components include aluminum oxide, silicon oxide, manganese oxide, and titanium oxide. They have high mechanical strength and a longer service life.

[0004] However, due to the different component characteristics of organic matter in different sewage, the effect of ozone catalysis in removing organic matter also varies greatly. Metal oxide-based ozone catalysts such as alumina-based have a higher micropore volume ratio and a hydrophilic surface, which tends to remove lower molecular weight and hydrophilic organic pollutants in water. In the study, the inventors found that the content of hydrophobic organic matter in reclaimed water accounts for 60%-80%, which is higher than that of hydrophilic organic matter. In addition, the molecular weight of organic matter is mostly in the molecular weight range of 1-10kDa. Therefore, it is urgent to develop a heterogeneous ozone catalyst targeting the characteristics of organic pollutants in reclaimed water, to achieve efficient removal of difficult-to-degrade organic matter in reclaimed water, and to provide support for improving the quality of reclaimed water and expanding the scope of reclaimed water utilization. Summary of the invention

[0005] The purpose of the present invention is to provide a composite molecular sieve ozone catalyst and its preparation method and application. According to the characteristics of hydrophilicity and molecular weight of the difficult-to-degrade organic matter in the reclaimed water, the ozone catalyst provided by the present invention has the specific adsorption and removal ability for the difficult-to-degrade organic matter in the reclaimed water, thereby improving the removal rate of the difficult-to-degrade organic matter in the reclaimed water.

[0006] In order to achieve the above object, the first aspect of the present invention provides a method for preparing a composite molecular sieve ozone catalyst, the preparation method comprising:

[0007] (1) mixing a molecular sieve powder with a low silicon-aluminum ratio and a salt solution of an active component, then heating and stirring the mixture to evaporate the solvent, and washing, drying, calcining and grinding the remaining solid to obtain a hydrophilic molecular sieve powder loaded with the active component;

[0008] (2) mixing the all-silicon molecular sieve powder and the NH4F aqueous solution, and subjecting the mixture to a hydrothermal reaction. After the reaction is completed, washing, drying, calcining and grinding the obtained solid material to obtain a fluorinated hydrophobic molecular sieve powder;

[0009] (3) mixing and granulating the hydrophilic molecular sieve powder loaded with active components, the fluorinated hydrophobic molecular sieve powder, the inorganic binder and the pore-forming agent to obtain spherical catalyst particles;

[0010] (4) Drying and calcining the spherical catalyst particles to obtain the composite molecular sieve ozone catalyst.

[0011] In the present invention, the washing in step (1) and step (2) is preferably rinsing.

[0012] According to the present invention, preferably, in step (1), the salt solution of the active component comprises: at least one of FeCl3 solution, Mn(NO3)2 solution, Ce(NO3)3 solution and La(NO3)3 solution;

[0013] The silicon-to-aluminum ratio of the molecular sieve powder with a low silicon-to-aluminum ratio is not higher than 30:1, and the minimum pore size is not lower than 0.7 nm; the molecular sieve powder with a low silicon-to-aluminum ratio is selected from SSZ-13 molecular sieve powder, ITQ-37 molecular sieve powder, MCM-56 molecular sieve powder, β-type molecular sieve powder or MOR-type molecular sieve powder.

[0014] According to the present invention, preferably, in step (1), the concentration of the salt solution of the active component is 0.1-0.5 mol / L;

[0015] The number of washings is 2-3 times;

[0016] The drying temperature is 40-60°C and the drying time is 4-12h;

[0017] The calcination temperature is 400-450°C and the calcination time is 4-8h;

[0018] The hydrophilic molecular sieve powder loaded with active components has a mesh size of 80-120.

[0019] According to the present invention, preferably, in step (2), the all-silicon molecular sieve powder is a Y-type molecular sieve powder or a β molecular sieve powder;

[0020] The concentration of the NH4F solution is 0.1-0.5 mol / L.

[0021] According to the present invention, preferably, in step (2), the mass ratio of NH4F to all-silicon molecular sieve powder is 1:(2-3);

[0022] The reaction temperature is 140-180°C, the reaction pressure is 2.5-4MPa, and the reaction time is 30-180min;

[0023] The number of washings is 2-3 times;

[0024] The drying temperature is 40-60°C and the drying time is 4-12h;

[0025] The calcination temperature is 400-450°C and the calcination time is 4-8h;

[0026] The fluorinated hydrophobic molecular sieve powder has a mesh size of 80-120.

[0027] According to the present invention, preferably, in step (3), the mass ratio of the fluorinated hydrophobic molecular sieve powder to the hydrophilic molecular sieve powder loaded with active components is (1.5-4):1;

[0028] The mass ratio of the inorganic binder to the hydrophilic molecular sieve powder loaded with active components is (0.05-0.2):1;

[0029] The mass ratio of the pore former to the hydrophilic molecular sieve powder loaded with active components is (0.1-0.3):1.

[0030] According to the present invention, preferably, in step (3), the inorganic binder is selected from one or two of pseudo-boehmite powder, calcium phosphate, sodium metasilicate, alumina sol, silica sol and kaolin;

[0031] The pore-forming agent is selected from one or two of ammonium bicarbonate, ammonium chloride, polystyrene microspheres, paraffin microspheres and polymethyl methacrylate microspheres;

[0032] Preferably, the pore-forming agent is composed of ammonium bicarbonate and polymethyl methacrylate microspheres, and the mass ratio of the ammonium bicarbonate to the polymethyl methacrylate microspheres is (1-2.5):1.

[0033] According to the present invention, preferably, in step (4), the drying temperature is 80-110° C., the drying time is not less than 12 h, and the moisture content of the material after drying is not higher than 5%;

[0034] The calcination temperature is 400-500° C. and the calcination time is 4-6 hours.

[0035] The second aspect of the present invention provides a composite molecular sieve ozone catalyst prepared by the above preparation method.

[0036] The third aspect of the present invention provides the use of the above-mentioned composite molecular sieve ozone catalyst in the removal of organic matter in reclaimed water.

[0037] The technical solution of the present invention has the following beneficial effects:

[0038] (1) The ozone catalyst provided by the present invention has the ability to specifically adsorb and remove the difficult-to-degrade organic matter in the reclaimed water, thereby improving the removal rate of the difficult-to-degrade organic matter in the reclaimed water.

[0039] (2) Since the heterogeneous ozone catalytic process is more inclined to remove hydrophilic and difficult-to-degrade organic matter, and the removal capacity of hydrophobic and difficult-to-degrade organic matter is relatively insufficient, the present invention synthesizes a molecular sieve-based ozone catalyst through a compounding strategy, and enhances the removal capacity of the process for hydrophobic and difficult-to-degrade organic matter by adding a certain proportion of hydrophobic molecular sieves. In addition, by measuring the proportion of hydrophobic components / hydrophilic components of organic matter in sewage, the proportion of hydrophilic and hydrophobic molecular sieves added in the catalyst formula can be adjusted. On top of this, the impregnation process can enhance the free radical output efficiency of the hydrophilic molecular sieve, while the fluorination process can further enhance the adsorption capacity of the hydrophobic molecular sieve, thereby further improving the removal efficiency of the catalyst for difficult-to-degrade organic matter.

[0040] (3) The composite molecular sieve ozone catalyst synthesized by the present invention forms a hierarchical pore structure of micropores-mesopores-macroporous by using 1 to 2 pore-forming agents selected from ammonium bicarbonate, ammonium chloride, polystyrene microspheres, paraffin microspheres and polymethyl methacrylate microspheres, compared with the traditional microporous molecular sieve substrate material. Since the optimal adsorption channel size of the adsorbent material for organic molecules in water is 2-3 times the diameter of the pollutant, and most of the organic molecules remaining in the reclaimed water are between 1k-10kDa (about 2-4nm in size), the mesoporous (2-50nm) structure in the ozone catalyst can effectively adsorb such organic matter, thereby improving the removal effect of organic matter. The macropores (above 50nm) in the ozone catalyst can improve the anti-fouling performance of the catalyst.

[0041] (4) The present invention synthesizes a composite molecular sieve ozone catalyst with both hydrophilic active sites and hydrophobic surface characteristics through an impregnation-blending two-step sintering process. Compared with the core-shell structure catalyst modified with a hydrophobic material surface, the density of Lewis acid active sites on the catalyst surface is effectively improved, and the efficiency of the reaction between ozone molecules and surface hydroxyl groups to produce hydroxyl radicals is promoted.

[0042] (5) The preparation method of the composite molecular sieve ozone catalyst described in the present invention uses a combined control strategy of a pore former and a binder, thereby ensuring that the material has a rich mesoporous volume structure while also enabling the ozone catalyst to have good mechanical strength and a high yield rate.

[0043] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] The above and other objects, features and advantages of the present invention will become more apparent through a more detailed description of exemplary embodiments of the present invention in conjunction with the accompanying drawings, wherein like reference numerals generally represent like components throughout the exemplary embodiments of the present invention.

[0045] Figure 1 A physical picture of a composite molecular sieve ozone catalyst according to an embodiment of the present invention is shown.

[0046] Figure 2 The molecular weight distribution diagram of organic matter in ultrafiltration effluent from a reclaimed water plant used in a test example according to the present invention is shown.

[0047] Figure 3 The figure shows the hydrophilic and hydrophobic components of the organic matter in the ultrafiltration effluent of the reclaimed water plant used in the test example of the present invention, wherein the total organic carbon is composed of hydrophobic organic carbon and hydrophilic organic carbon. DETAILED DESCRIPTION

[0048] The preferred embodiments of the present invention will be described in more detail below. Although the preferred embodiments of the present invention are described below, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided to make the present invention more thorough and complete, and to fully convey the scope of the present invention to those skilled in the art.

[0049] The present invention is further described below by examples:

[0050] The average particle size of the β-type molecular sieve powder used in the following examples and comparative examples is 150 um; the average particle size of the Y-type all-silicon molecular sieve powder is 150 um; and the polymethyl methacrylate microspheres are purchased from Beijing Zhongke Keyou Technology Co., Ltd.

[0051] Example

[0052] This embodiment provides a composite molecular sieve ozone catalyst, and the specific preparation method is as follows:

[0053] (1) Preparation of hydrophilic molecular sieve powder loaded with active components: Take 100 g of β-type molecular sieve powder with a silicon-aluminum ratio of 30:1 (the minimum pore size is 1 nm), pour it into a container containing 1250 ml of 0.5 mol / L Mn(NO3)2 aqueous solution, stir and mix well, and then use ultrasound to evenly distribute it for more than 2 hours; place the mixed mixture on a heating magnetic stirrer, and keep the mixed solution under 70°C insulation conditions for continuous and slow stirring to allow the water to evaporate slowly; place the remaining solid obtained by immersion in deionized water and rinse it repeatedly for 3 times, and then place the rinsed solid in a dryer at 60°C and dry it for 5 hours; place the dried solid in a calcining furnace and heat it up, the heating rate is 5°C / min, the heating end temperature is 450°C, and the insulation time is 6 hours; after the insulation time is over, wait for natural cooling, take it out after it drops to room temperature, grind the solid and pass it through a 100-mesh sieve to obtain a hydrophilic molecular sieve powder loaded with active components.

[0054] (2) Preparation of fluorinated hydrophobic molecular sieve: 11 g of Y-type all-silicon molecular sieve powder was poured into a Teflon-lined autoclave, and 200 mL of 0.5 mol / L NH4F aqueous solution was added to the autoclave, stirred and mixed, and then the equipment was closed, heated and pressurized, and the powder was subjected to high-pressure hydrothermal reaction at 150°C for 150 min in the autoclave, and the reaction pressure was 3 MPa. After the reaction, the autoclave was cooled and depressurized, and the obtained solid material was repeatedly rinsed in deionized water for 3 times, and the rinsed solid was dried at 60°C for 5 h, and the dried solid was placed in a calcining furnace for heating and calcination, with a heating rate of 5°C / min, an end temperature of 450°C, and a heat preservation time of 5 h. After the heat preservation time, it was allowed to cool naturally, and was taken out after it cooled to room temperature. The solid was ground and passed through a 100-mesh sieve to obtain a fluorinated hydrophobic molecular sieve powder.

[0055] (3) Compounding of molecular sieves and mixing and granulation of additives: The hydrophilic molecular sieve powder loaded with active components, the fluorinated hydrophobic molecular sieve powder, pseudo-boehmite powder, ammonium bicarbonate and polymethyl methacrylate microspheres are mixed in a mass ratio of 40:120:5:8:4, and dry-blended and granulated in a granulator to obtain a spherical catalyst precursor.

[0056] (4) Curing and activation of spherical catalyst: The spherical catalyst precursor prepared in the previous step is placed in a dryer for drying at a temperature of 80°C for 12 hours. The moisture content of the dried material is not higher than 5%. The dried spherical catalyst is sent to an electric furnace for calcination at a temperature of 500°C for 6 hours. After the calcination, the material is allowed to cool naturally. After cooling to room temperature, it is taken out to obtain ozone catalyst particles (such as Figure 1 shown).

[0057] The composite molecular sieve ozone catalyst prepared in the embodiment was tested, and the specific test results are shown in Table 1, wherein the pore structure of the catalyst was analyzed by Brunauer-Emmett-Teller (BET) using a specific surface area analyzer (USA, Micromeritics ASAP 2460), and the test data of porosity, specific surface area, total pore volume, mesopore volume, and micropore volume were obtained; the mechanical strength was tested using a particle strength tester (Dalian Intelligent Testing Machine Factory, ZQJ-Ⅲ); the wear rate was tested using a friction and wear tester (MFT5000).

[0058] Table 1 Catalyst material properties prepared in this example

[0059]

[0060] It can be seen from Table 1 that the ozone catalyst prepared in the present invention has abundant mesopore volume and high mechanical strength.

[0061] Comparative Example 1

[0062] Mixing and granulation of molecular sieve and additives: The hydrophilic molecular sieve powder loaded with active components prepared in step (1) of Example, pseudo-boehmite powder, ammonium bicarbonate and polymethyl methacrylate microspheres are mixed in a mass ratio of 40:5:8:4, and dry-mixed and granulated in a granulator to obtain a spherical catalyst precursor.

[0063] Curing and activation of the spherical catalyst: the spherical catalyst precursor prepared in the previous step is placed in a dryer for drying at a drying temperature of 80°C for 12 hours, and the moisture content of the dried material is not higher than 5%; the dried spherical catalyst is sent to an electric furnace for calcination at a calcination temperature of 500°C for 6 hours; after the calcination is completed, the material is allowed to cool naturally, and is taken out after cooling to room temperature to obtain a hydrophilic ozone catalyst (AC-1).

[0064] Comparative Example 2

[0065] Mixing and granulation of molecular sieve and additives: The fluorinated hydrophobic molecular sieve powder, pseudo-boehmite powder, ammonium bicarbonate and polymethyl methacrylate microspheres prepared in step (2) of Example are mixed in a mass ratio of 120:5:8:4, and dry-mixed and granulated in a granulator to obtain a spherical catalyst precursor.

[0066] Curing and activation of the spherical catalyst: the spherical catalyst precursor prepared in the previous step is placed in a dryer for drying at a temperature of 80°C for 12 hours, and the moisture content of the dried material is not higher than 5%; the dried spherical catalyst is sent to an electric furnace for calcination at a temperature of 500°C for 6 hours; after the calcination, the material is allowed to cool naturally, and taken out after cooling to room temperature to obtain a hydrophobic ozone catalyst (AC-2).

[0067] Comparative Example 3

[0068] Mixing and granulation of molecular sieve and additives: The hydrophilic molecular sieve powder loaded with active components prepared in step (1) of Example, pseudo-boehmite powder, ammonium bicarbonate and polymethyl methacrylate microspheres are mixed in a mass ratio of 40:5:8:4, and dry-mixed and granulated in a granulator to obtain a spherical catalyst precursor.

[0069] Curing and activation of the spherical catalyst: the spherical catalyst precursor prepared in the previous step is placed in a dryer for drying at a drying temperature of 80°C for 12 hours, and the moisture content of the dried material is not higher than 5%; the dried spherical catalyst is sent to an electric furnace for calcination at a calcination temperature of 500°C for 6 hours; after the calcination is completed, the material is allowed to cool naturally, and is taken out after cooling to room temperature to obtain a hydrophilic ozone catalyst (AC-1).

[0070] Take 0.2g of polytetrafluoroethylene emulsion (PTFE emulsion), add 120g of deionized water, add 0.5g of silicon nitride thereto, stir evenly, add 50g of AC-1 catalyst, let stand for 10min, filter out the catalyst, place the filtered catalyst in a muffle furnace, and in an air environment, increase the temperature to 350°C at a heating rate of 10°C / min, and continue calcining at 350°C for 30min to obtain the final hydrophobic coating modified ozone catalyst (AC-3).

[0071] Test Case

[0072] Water quality characteristics of the original water sample to be tested:

[0073] The molecular weight distribution of organic matter and the characteristics of hydrophilic and hydrophobic components of ultrafiltration effluent from a reclaimed water plant in Beijing are as follows: Figure 2 and Figure 3As shown. The molecular weight distribution was detected by high performance liquid chromatography, ultraviolet detector (detection wavelength 254nm) and gel chromatography column, the mobile phase was a phosphate buffer solution prepared by sodium dihydrogen phosphate and dipotassium hydrogen phosphate, and the flow rate was 0.6mL / min; the hydrophilic and hydrophobic components were detected by macroporous adsorption resin, anion and cation exchange resin, and gel exclusion chromatography column separation method to separate the soluble organic matter in water into hydrophilic and hydrophobic soluble organic matter components, and the total organic carbon analyzer was used for quantitative detection.

[0074] The performance of the composite molecular sieve ozone catalyst (BDCO) prepared in Example 1, the hydrophilic ozone catalyst (AC-1) prepared in Comparative Example 1, the hydrophobic ozone catalyst (AC-2) prepared in Comparative Example 2, and the hydrophobic coating modified ozone catalyst (AC-3) prepared in Comparative Example 3 were evaluated, and the specific evaluation method is as follows:

[0075] Evaluation method: The compound molecular sieve ozone catalyst (BDCO), hydrophilic ozone catalyst (AC-1), hydrophobic ozone catalyst (AC-2) and hydrophobic coating modified ozone catalyst (AC-3) were respectively loaded into the organic glass reaction column with a diameter of 18cm, a height of 2.4m, a total volume of 61L, a catalyst loading height of 0.8m, and a volume of 20L. The ozone inlet concentration was 50mg / L, the ozone inlet flow rate was 0.2L / min, and ozone was introduced from the titanium aeration plate at the bottom of the reactor; the raw water was the ultrafiltration effluent of a certain recycled water plant in Beijing mentioned above, the inlet flow rate was 50L / h, and the empty bed residence time was 20min. The inlet and outlet water were taken 3 times at intervals of 30min, the chemical oxygen demand (COD) was detected, and the average value was calculated. The determination of chemical oxygen demand (COD) was carried out according to the "Determination of Chemical Oxygen Demand of Water Quality by Dichromate Method" (HJ828-2017).

[0076] The experimental results of COD removal from reclaimed water using the composite molecular sieve ozone catalyst (BDCO) prepared in the embodiment show that the COD concentration is significantly reduced after ozone catalytic treatment. When the ozone dosage is 15 mg / L, the COD is reduced from the initial state of 26.8 mg / L to 13.1 mg / L, and the removal rate is 51.1%. The ratio of the amount of ozone consumed to the unit COD removed is 1.09.

[0077] The experimental results of COD removal from reclaimed water using a hydrophilic ozone catalyst (AC-1) show that the COD concentration is slightly reduced after ozone catalytic treatment. When the ozone dosage is 15 mg / L, the COD is reduced from the initial state of 26.5 mg / L to 18.2 mg / L, and the removal rate is 31.3%. The ratio of the amount of ozone consumed to the unit COD removed is 1.81. Compared with the composite molecular sieve ozone catalyst prepared by the present invention, the COD removal rate is about 20% lower.

[0078] The experimental results of COD removal from reclaimed water using a hydrophobic ozone catalyst (AC-2) show that the COD concentration is slightly reduced after ozone catalytic treatment. When the ozone dosage is 15 mg / L, the COD is reduced from the initial state of 27.4 mg / L to 21.6 mg / L, and the removal rate is 21.2%. The ratio of the amount of ozone consumed to the unit COD removed is 2.59. Compared with the composite molecular sieve ozone catalyst prepared by the present invention, the COD removal rate is about 30% lower.

[0079] The experimental results of COD removal of reclaimed water using ozone catalyst (AC-3) modified by hydrophobic coating show that after ozone catalytic treatment, COD concentration is slightly reduced. When the ozone dosage is 15mg / L, COD is reduced from 27.8mg / L in the initial state to 18.2mg / L, and the removal rate is 34.5%. The ratio of the amount of ozone consumed to the removal of unit COD is 1.56, and the COD removal rate is about 17% lower than that of the composite molecular sieve ozone catalyst prepared by the present invention. It can be seen from this that the ozone catalyst modified by the above-mentioned hydrophobic coating is wrapped in the surface of the hydrophilic catalyst using a hydrophobic material to form a core-shell structure. Although the ozone wettability of the catalyst surface is improved and better contacted with ozone, the abundance of hydrophilic active sites is reduced, and the free radical generation efficiency decreases. Therefore, compared with the catalyst of the present invention, the COD removal rate is significantly lower.

[0080] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.

Claims

1. A method for preparing a composite molecular sieve ozone catalyst, characterized in that: The preparation method comprises: (1) mixing a molecular sieve powder with a low silicon-aluminum ratio and a salt solution of an active component, then heating and stirring the mixture to evaporate the solvent, and washing, drying, calcining and grinding the remaining solid to obtain a hydrophilic molecular sieve powder loaded with the active component; (2) mixing the all-silicon molecular sieve powder and the NH4F aqueous solution, and subjecting the mixture to a hydrothermal reaction. After the reaction is completed, washing, drying, calcining and grinding the obtained solid material to obtain a fluorinated hydrophobic molecular sieve powder; (3) mixing and granulating the hydrophilic molecular sieve powder loaded with active components, the fluorinated hydrophobic molecular sieve powder, the inorganic binder and the pore-forming agent to obtain spherical catalyst particles; (4) Drying and calcining the spherical catalyst particles to obtain the composite molecular sieve ozone catalyst.

2. The preparation method according to claim 1, wherein In step (1), the salt solution of the active component includes at least one of: FeCl3 solution, Mn(NO3)2 solution, Ce(NO3)3 solution and La(NO3)3 solution; The silicon-to-aluminum ratio of the molecular sieve powder with a low silicon-to-aluminum ratio is not higher than 30:1, and the minimum pore size is not lower than 0.7 nm; the molecular sieve powder with a low silicon-to-aluminum ratio is selected from SSZ-13 molecular sieve powder, ITQ-37 molecular sieve powder, MCM-56 molecular sieve powder, β-type molecular sieve powder or MOR-type molecular sieve powder.

3. The preparation method according to claim 1, wherein In step (1), the concentration of the salt solution of the active component is 0.1-0.5 mol / L; The number of washings is 2-3 times; The drying temperature is 40-60°C and the drying time is 4-12h; The calcination temperature is 400-450°C and the calcination time is 4-8h; The hydrophilic molecular sieve powder loaded with active components has a mesh size of 80-120.

4. The preparation method according to claim 1, wherein In step (2), the all-silicon molecular sieve powder is a Y-type molecular sieve powder or a β-type molecular sieve powder; The concentration of the NH4F solution is 0.1-0.5 mol / L.

5. The preparation method according to claim 1, wherein In step (2), the mass ratio of NH4F to all-silicon molecular sieve powder is 1:(2-3); The temperature of the hydrothermal reaction is 140-180°C, the reaction pressure is 2.5-4MPa, and the reaction time is 30-180min; The number of washings is 2-3 times; The drying temperature is 40-60°C and the drying time is 4-12h; The calcination temperature is 400-450°C and the calcination time is 4-8h; The fluorinated hydrophobic molecular sieve powder has a mesh size of 80-120.

6. The preparation method according to claim 1, wherein In step (3), the mass ratio of the fluorinated hydrophobic molecular sieve powder to the hydrophilic molecular sieve powder loaded with active components is (1.5-4):1; The mass ratio of the inorganic binder to the hydrophilic molecular sieve powder loaded with active components is (0.05-0.2):1; The mass ratio of the pore former to the hydrophilic molecular sieve powder loaded with active components is (0.1-0.3):

1.

7. The preparation method according to claim 1, wherein In step (3), the inorganic binder is selected from one or two of pseudo-boehmite powder, calcium phosphate, sodium metasilicate, alumina sol, silica sol and kaolin; The pore-forming agent is selected from one or two of ammonium bicarbonate, ammonium chloride, polystyrene microspheres, paraffin microspheres and polymethyl methacrylate microspheres; Preferably, the pore-forming agent is composed of ammonium bicarbonate and polymethyl methacrylate microspheres, and the mass ratio of the ammonium bicarbonate to the polymethyl methacrylate microspheres is (1-2.5):

1.

8. The preparation method according to claim 1, wherein In step (4), the drying temperature is 80-110° C., the time is not less than 12 hours, and the moisture content of the material after drying is not higher than 5%; The calcination temperature is 400-500° C. and the calcination time is 4-6 hours.

9. A composite molecular sieve ozone catalyst prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the composite molecular sieve ozone catalyst according to claim 9 in removing organic matter from reclaimed water.

Citation Information

Cited By

  • Preparation method and application of soapstone / TiO2 particle composite catalyst with mesoporous-macroporous two-stage aperture structure

    CN121103342A

  • A pollution-resistant intelligent response type ozone catalytic oxidant and a preparation method thereof

    CN122768984A

  • Compound molecular sieve ozone catalyst, and preparation method therefor and use thereof

    WO2026123862A1